Angka Kejadian Komplikasi Lambat Pascaoperasi Prostatektomi Transvesikal dan Reseksi Transuretral pada Pasien Pembesaran Prostat Jinak - Bakri Hasbullah (Biomedika, 2009)
Transurethral Resection Prostatectomy (TURP) and Transvesical Prostatectomy (TVP) are the two methods of operation for BPH. The aims of this study are to find out the late complication after prostatectomy between TVP dan TURP. Data were collected from January 1 st 2004 to December 31 st 2004 with prospective cohort study. There were 67 of 90 post prostatectomy BPH patients who met the inclusion criteria. Data were listed into age and comorbid factors are hypertension (HT), ischaemic heart disease (IHD), chronic obstructive pulmonary disease (COPD), Diabetes Mellitus (DM). Post prostatectomy late complications are erectile dysfunction (ED), retrograde ejaculation (RE), urethral stricture (US), urinary incontinence (UI). Data were analyzed statistically with the t-test. There were 67 patients (median age 65,81 years range 51-86 years) inclusion in this study 12 patients has performed TVP (17,9%), 55 patient was performed TURP (82,1%). Comorbid factors were HT (19,4%), IHD (16,4%), COPD (11,9%), DM (4,5%). The most frequent age of TVP were 7 th decade (50%), TURP were 6 th decade (41,82%).The late complication after TVP and TURP for BPH were not significant different (p0,05). The most frequent late complications after prostatectomy of the TVP and TURP is ED. Study about the late complications after operation of the BPH between TVP and TURP, statistically were not significantly different.Keywords: BPH, open prostatectomy, TURP, late complication.